Peran Filsafat Ilmu dalam Perkembangan Bahasa dan Implikasinya terhadap Pendidikan - Mardi, Melia; Putri, Desmimi Eka; Yasmanelly, Yasmanelly; Fauziati, Fauziati; Isesmazurita, Isesmazurita; Marsis, Marsis (Jurnal Bahastra, 2025)
The philosophy of language is an intricate and expansive field that defies narrow definitions due to its deep entrenchment within the broader framework of philosophical inquiry. Its scope extends across nearly every domain of knowledge, making it a foundational yet complex subject of study. This article addresses the essential nature of language by treating it as a central object of philosophical investigation. The primary research question posed is: "What is the philosophical nature of language when approached as an autonomous object of inquiry?" Using a conceptual and descriptive-analytical method, the study examines language's ontological and epistemological dimensions. The findings suggest that language in philosophy is not merely a medium of communication but a constitutive element of thought, meaning, and reality construction. This aligns with other branches of philosophy—such as the philosophy of law, nature, human existence, and society—which similarly treat their core concepts as independent objects of scrutiny. The article concludes that the philosophy of language offers a distinctive yet integrative lens for understanding human cognition, knowledge systems, and cultural structures.